John Day's Production of Woodcut Prints from John Foxe's Acts and Monuments. (10th March 2022) - Rankin, Mark
Abstract: Scholars have long suspected the existence of John Day's independent commercial trade in woodcut prints from the illustrations of Foxe's Acts and Monuments . This essay supplies bibliographical evidence in support of this hypothesis. The evidence consists of changes in typesetting found within the textblocks and captions used to identify the images, as well as deterioration patterns discernable within Foxe woodcuts used from the first (1563) to seventh (1631–32) editions of Acts and Monuments . By examining surviving examples of prints which Day included within successive editions, the analysis reveals that some prints are almost certainly not original to Day's manufacture of the books which now preserve them, or to any other known early edition. Instead, some copies of these prints appear to have been inserted within books at the time of manufacture, most likely by Day, who drew upon a pre-existing stock of prints which he had independently manufactured.